2020
DOI: 10.1113/jp280481
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of renal oxygen metabolism during low Na+ diet: effect of angiotensin II AT1 and aldosterone receptor blockade

Abstract: Reducing Na + intake reduces the partial pressure of oxygen in the renal cortex and activates the renin-angiotensin-aldosterone system. r In the absence of high blood pressure, these consequences of dietary Na + reduction may be detrimental for the kidney. r In a normotensive animal experimental model, reducing Na + intake for 2 weeks increased renal oxygen consumption, which was normalized by mineralocorticoid receptor blockade. Furthermore, blockade of the angiotensin II AT 1 receptor restored cortical parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 63 publications
(163 reference statements)
0
4
0
Order By: Relevance
“…Moreover, Ang II stimulates Na + transporter abundance and activity, particularly in the distal nephron [ 48 ] where T Na /Q O2 is lower, which also raises O 2 consumption. Palm and colleagues recently demonstrated that activation of the renin-angiotensin-aldosterone system by a low Na + diet increased Q O2 and lowered cortical pO 2 but raised medullary pO 2 [ 49 ]; a similar low-salt diet-induced reversal of pO 2 gradients was previously observed [ 50 ]. Of note, AT1 receptor blockade restored pO 2 without reducing Q O2 , confirming the major impact of Ang II on renal O 2 delivery [ 49 ].…”
Section: Renal Oxygenationmentioning
confidence: 81%
“…Moreover, Ang II stimulates Na + transporter abundance and activity, particularly in the distal nephron [ 48 ] where T Na /Q O2 is lower, which also raises O 2 consumption. Palm and colleagues recently demonstrated that activation of the renin-angiotensin-aldosterone system by a low Na + diet increased Q O2 and lowered cortical pO 2 but raised medullary pO 2 [ 49 ]; a similar low-salt diet-induced reversal of pO 2 gradients was previously observed [ 50 ]. Of note, AT1 receptor blockade restored pO 2 without reducing Q O2 , confirming the major impact of Ang II on renal O 2 delivery [ 49 ].…”
Section: Renal Oxygenationmentioning
confidence: 81%
“…The study by Patinha et al . (2020) published in this issue of The Journal of Physiology addresses RAAS‐mediated adaptive changes to a 10‐fold salt restriction, involving the renal microcirculation, tubular sodium handling and oxygen expenditure, providing novel perspectives on the control of renal oxygenation.…”
mentioning
confidence: 99%
“…Patinha et al . (2020) report that extreme salt depletion in normotensive rats reduces cortical oxygenation and increases sodium retention, oxygen consumption and extraction with decreased transport work efficacy. Assessing the role of activated RAAS in these changes, they found that candesartan infused into the renal artery did not affect blood pressure and GFR but restored cortical oxygenation, principally by increasing renal blood flow and oxygen delivery.…”
mentioning
confidence: 99%
See 1 more Smart Citation